A Note on Passive-Like Statives in Quechua - Muysken, Pieter (Revue québécoise de linguistique)

(untitled) (Université du Québec à Montréal, 1986)
AbstractIn this note I try to provide an analysis of passive-like stative constructions in Quechua which starts out from the idea that there are not just two types of chains in syntactic representations: A ( = argument) - chains and Ā ( = operator) - chains, but a third type as well: predication chains. The analysis is a substantial improvement over earlier ones and leads us to a preliminary account of the formal properties of predication chains.